Unraveling the Epidemiology, Geographical Distribution, and Genomic Evolution of Potentially Lethal Coronaviruses (SARS, MERS, and SARS CoV-2) - Masood, Nosheen; Malik, Saima Shakil; Raja, Muhammad Naqqi; Mubarik, Sumaira; Yu, Chuanhua (Frontiers in Cellular and Infection Microbiology, 2020)
SARS CoV appeared in 2003 in China, transmitted from bats to humans via eating infected animals. It affected 8,096 humans with a death rate of 11% affecting 21 countries. The receptor binding domain (RBD) in S protein of this virus gets attached with the ACE2 receptors present on human cells. MERS CoV was first reported in 2012 in Middle East, originated from bat and transmitted to humans through camels. MERS CoV has a fatality rate of 35% and last case reported was in 2017 making a total of 1,879 cases worldwide. DPP4 expressed on human cells is the main attaching site for RBD in S protein of MERS CoV. Folding of RBD plays a crucial role in its pathogenesis. Virus causing COVID-19 was named as SARS CoV-2 due its homology with SARS CoV that emerged in 2003. It has become a pandemic affecting nearly 200 countries in just 3 months’ time with a death rate of 2-3% currently. The new virus is fast spreading, but it utilises the same RBD and ACE2 receptors along with furin present in human cells. It may be expected that as the SARS CoV appeared once and never returned again similarly COVID-19 may not appear again unlike MERS CoV due its remarkable similarity with SARS CoV that is presented in this report.